Revealing The Relationship Between Audit Tenure, Auditor Switching, And Firm Age On Audit Report Lag In Consumer Non-Cyclicals Companies - Bintang, Avriana Septian Mutiara; Triyuwono, Iwan (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
This study examines the effect of audit tenure, auditor switching, and company age on audit report lag. The object of this research is a non-cyclical consumer sector company listed on the Indonesia Stock Exchange with a total of three years. The sample in this study were 81 samples. The research method used is a quantitative approach, namely hypothesis testing. The data testing method uses panel data regression. The results show that audit tenure has a positive effect on audit report lag, while auditor switching and company age have no effect. The longer the company engages with KAP, the longer the audit report lag will be. Simultaneously, audit tenure, auditor switching, and company age affect audit report lag. The coefficient of determination is 6.58%, indicating that the three independent variables can influence the dependent variable only by 6.58%.